Scientometric Research Mapping of OMICRON for Scientific Production: A Global Perception Analysis - Satish S; Sylvia Grace J; Vasna Joshua; Prabakaran M (Medsci Publications, 2023)
Background: South Africa reported a new variant of SARS-CoV-2, named 'Omicron,' to the World Health Organization on November 24, 2021. Scientometric analysis quantify all currently available written communication, the authors of that communication, and their citation analysis. The study's goal was to use the Scopus and Web of Science databases to look at the research metrics of Omicron publications published between January 1965 and March 2020. Methods: All scientific research outputs with the word 'Omicron' in the title were retrieved from the Web of Science (January 1965 to March 2022) and Scopus (January 1896 to March 2022) databases on April 10, 2022. The data was analyzed based on year-wise publications; leading authors; predominant journals in publishing, highly cited articles with citations; type of publications; subject classification, frequently used keywords, geographical distribution of publication, language, and more contributed institutions. Results: There were 1229 research outputs for WoS and 655 from Scopus. The number of publications for WoS increased from 22 in 1965 to 265 in 2022, while Scopus increased from 1 in 1896 to 356 in 2022. Both the databases identified the author Yuen KY as the highest contributor; Journal of Virology and Nature as the predominant journals; the Lancet as highly cited journal; majority as original articles; frequently used keywords as 'SARS-CoV-2'; the United States of America as the most productive country; majority publication in English. The publications were mainly on the subjects Chemistry and Medicine by WoS and Scopus, respectively. The most productive institute was the 'University of California Systems' by WoS and the 'University of Hong Kong' by Scopus. Conclusion: The term 'Omicron' first appeared in the domain of Chemistry in the late 18th century. The growth pattern of publication was not consistent. The above research metrics will be helpful to researchers in the coming days.